2022
DOI: 10.3390/molecules27030791
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Route to Produce Highly Efficient Porous Carbons Recycled from Tea Waste for High-Performance Symmetric Supercapacitor Electrodes

Abstract: High-performance porous carbons derived from tea waste were prepared by hydrothermal treatment, combined together with KOH activation. The heat-treatment-processed materials possess an abundant hierarchical structure, with a large specific surface of 2235 m2 g−1 and wetting-complemental hydrophilicity for electrolytes. In a two-electrode system, the porous carbon electrodes’ built-in supercapacitor exhibited a high specific capacitance of 256 F g−1 at 0.05 A g−1, an excellent capacitance retention of 95.4% aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Comparison of the average current densities revealed an increase in current output (mA/m discussed above (Figure 2(c)). Recent studies have also reported improved current performance for STL and reported mild antimicrobial properties of SCG that could affect microbial metabolism [19,21,29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the average current densities revealed an increase in current output (mA/m discussed above (Figure 2(c)). Recent studies have also reported improved current performance for STL and reported mild antimicrobial properties of SCG that could affect microbial metabolism [19,21,29].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, STL and SCG are potential energy sources enriched with carbonderivatives such as alkaloids and polyphenols (STL) and organic compounds including fatty acids, hemicelluloses, lignin, cellulose, and other polysaccharides (SCG) [14,15]. Recent studies have highlighted the potential of SCG and STL as a source of sugars [16], bioethanol [17], and biodiesel [18], and some studies have exploring the use of STL and SCG for fabricating electrodes [19][20][21]. In this context, STL and SCG are promising options for use in MESs to reduce the carbon footprint and energy consumption associated with electrode manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous mining of fossil fuels has contributed to global weather warming while the need for energy in human daily lives is constantly increasing. [1][2][3] To address these issues, the development and research of electrochemical energy storage system are quietly necessary. [4][5][6] A supercapacitor, a kind of outstanding energy storage device, can bridge the gap between batteries and conventional capacitors.…”
Section: Introductionmentioning
confidence: 99%